Co-operation of MCL-1 and BCL-XL anti-apoptotic proteins in stromal protection of MM cells from carfilzomib mediated cytotoxicity - Galas-Filipowicz, Daria; Chavda, Selina J.; Gong, Jia-Nan; Huang, David C. S.; Khwaja, Asim; Yong, Kwee (Frontiers in Oncology, 2024)
Introduction: BCL-2 family proteins are important for tumour cell survival and drug resistance in multiple myeloma (MM). Although proteasome inhibitors are effective antimyeloma drugs, some patients are resistant and almost all eventually relapse. We examined the function of BCL-2 family proteins in stromal-mediated resistance to carfilzomib-induced cytotoxicity in MM cells.Methods: Co-cultures employing HS5 stromal cells were used to model the interaction with stroma. MM cells were exposed to CFZ in a 1-hour pulse method. The expression of BCL-2 family proteins was assessed by flow cytometry and WB. Pro-survival proteins: MCL-1, BCL-2 and BCL-XL were inhibited using S63845, ABT-199 and A-1331852 respectively. Changes in BIM binding partners were examined by immunoprecipitation and WB.Results: CFZ induced dose-dependent cell death of MM cells, primarily mediated by apoptosis. Culture of MM cells on HS-5 stromal cells resulted in reduced cytotoxicity to CFZ in a cell contact-dependent manner, upregulated expression of MCL-1 and increased dependency on BCL-XL. Inhibiting BCL-XL or MCL-1 with BH-3 mimetics abrogated stromal-mediated protection only at high doses, which may not be achievable in vivo. However, combining BH-3 mimetics at sub-therapeutic doses, which alone were without effect, significantly enhanced CFZ-mediated cytotoxicity even in the presence of stroma. Furthermore, MCL-1 inhibition led to enhanced binding between BCL-XL and BIM, while blocking BCL-XL increased MCL-1/BIM complex formation, indicating the cooperative role of these proteins.Stromal interactions alter the dependence on BCL-2 family members, providing a rationale for dual inhibition to abrogate the protective effect of stroma and restore sensitivity to CFZ.